The INFLUENCE OF INFLUENCER MARKETING AND SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS AT TEANOL CAFÉ, JELUTUNG BRANCH, JAMBI CITY - Simarmata, Lusiana Pransisca; Ekasari, Novita; Novitasari, Novitasari (Journal of Business Studies and Management Review, 2025)
This study aims to determine the effect of Influencer Marketing and Social Media Marketing on Purchasing Decisions at Café Teanol, Jelutong Branch, Jambi City. This study uses quantitative methods and data collection techniques by distributing questionnaires using a Likert scale. The type of data used is primary data obtained from filling out questionnaires via Google Forms. The data analysis method used is multiple linear analysis using SPSS version 27. The sample in this study were consumers who made purchases at Café Teanol, Jelutung Branch, Jambi City, as many as 98 respondents with a purposive sampling method. The results show that Influencer Marketing and Social Media Marketing have a positive and significant effect on purchasing decisions both simultaneously and partially, and the variable that dominates in influencing is Influencer Marketing. Suggestions for Café Teanol Jelutung Branch are expected to improve and choose Influencers with more social media accounts to increase consumer trust, teanol is also expected to encourage consumers to share product posts on café teanol so that more people know about the posts, and teanol is expected to increase consumer satisfaction to have a good experience and will make consumers tell their experiences to potential consumers so that purchasing decisions occur